PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN BERAS MERAH DI PASAR TEMBOK SURABAYA - Ramon Syahrial; Oscarius Yudhi Ari Wijaya (ITB AAS INDONESIA Surakarta, 2021)
The method uses analysis in the form of test equivalence, reliability test, multiple linear regression, coefficient of determination and hypothesis testing with the f test and the T test with the help of the program (SPSS) 16.0. Based on the results of the analysis, the regression equation Y = 0.150 + 0.365X1 + 0.370X2 + 0.390X3 + 0.433X4 + e constant is 0.150. meaning that if the free value is 0, then the Y value is 0.150 with the coefficient of cultural variables (X1) of 0.365, social (X2) of 0.370, personal (X3) of 0.390 and psychological (X4) of 0.433 which means that it is positive. From the results of the t hypothesis test, it was obtained that the tcount of cultural variables was 2.562, social variables were 1.911, personal variables were 1.715, and psychological variables were 1.542. Only cultural variables have an effect with a value of 2.562 so that the tcount> is compared with the ttable value of 2.05954. Based on the simultaneous F test, the value of Fcount is 5,628> F table 2,7822 and the significance is 0,000